Participation as user involvement - Landert, Daniela (Handbooks of pragmatics ; volume 11: Pragmatics of social media, 2017)
Das Kapitel 2. Participation as user involvement erschien in Pragmatics of Social Media auf Seite 31.
Gesehen am 04.04.2024